Can investments sustain China’s economic growth? - Chow, Ho Ming. (2010)
The ability of China to maintain a growth rate between 7 and 10 % for the past 30 years has been a formidable feat, bringing itself to the international limelight. It has come to notice that investments played a large role in China’s economic growth. This paper aims to find out the sustainability of investments in maintaining China’s growth with the use of a simple accounting growth model, the Cobb Douglas function.